Android application for file storage and retrieval over secured and distributed file servers - Kukkadapu, Sowmya (Kansas State University, 2012)
Recently, the world has been trending toward the use of Smartphone. Today, almost each and every individual is using Smartphone for various purposes benefited by the availability of large number of applications. The memory on the SD (Secure Digital) memory card is going to be a constraint for the usage of the Smartphone for the user. Memory is used for storing large amounts of data, which include various files and important document. Besides having many applications to fill the free space, we hardly have an application that manages the free memory according to the user’s choice. In order to manage the free space on the SD card, we need an application to be developed. All the important files stored on the Android device cannot be retrieved if we lose the Android device. Targeting the problem of handling the memory issues, we developed an application that can be used to provide the security to the important documents and also store unnecessary files on the distributed file servers and retrieve them back on request.
Keywords: Android application; Distributed systems; File transfer; Mobile-to-computer; Distributed file servers; Computer Science (0984)